Actions for damages in EU law: A comparative analysis of the liability of EU institutions and the liability of member states - Adao?lu, Hacer Soykan (TURKIYE ORTADOGU AMME IDARES IENSTITUSU todaie@todaie.gov.tr, 2016)
The rule of law requires that the legality of the actions of administration must be supervised, and individuals must be compensated for any illegal actions of administration. The actions of both the EU institutions and member states should be in conformity with EU law. Individuals, who suffer a damage resulting from the breach of EU law, can bring actions against the EU institutions before the EU courts and against member states before national courts. The aim of this paper is to examine the actions for damages at EU and national level, and to compare the liability of EU institutions and member states in terms of legal bases, content, conditions, and outcomes.
Avrupa Birli?i Hukukunda Tam Yargi Davalari: AB Kurumlari ve Üye Devletlerin Sorumluluklarinin Karşilaştirilmasi
Keywords: Action for damages; Compensation; Liability